The Usefulness of the BD MAX MDR-TB Molecular Test in the Rapid Diagnosis of Multidrug-Resistant Tuberculosis - Tomasz Bogiel; Edyta Dolska; Małgorzata Zimna; Kornelia Nakonowska; Dorota Krawiecka; Renata Żebracka; Maciej Pochowski; Agnieszka Krawczyk (Pathogens, 2025)
Tuberculosis (TB), primarily caused by Mycobacterium tuberculosis complex (MTBC), remains a global health challenge and can lead to severe pulmonary and extrapulmonary complications. Multidrug-resistant TB (MDR-TB) poses additional challenges, requiring advanced diagnostic and treatment strategies. This study evaluates the BD MAX MDR-TB molecular test for a rapid diagnosis of MDR-TB, detecting resistance to rifampicin (RIF) and isoniazid (INH). The BD MAX MDR-TB test, utilizing real-time PCR, was used to analyze specimens collected from TB-suspected patients, identifying MTB DNA and mutations associated with rifampicin and isoniazid resistance. Results were compared with traditional drug susceptibility testing, and 79 out of 638 samples tested were positive for MTB DNA, with 65 showing a sufficient amount of genetic material for resistance gene identification. The BD MAX test showed a 100% correlation with phenotypic rifampicin resistance, though discrepancies were noted for isoniazid resistance, with a 93% concordance. The BD MAX MDR-TB test is an effective tool for a rapid diagnosis of MDR-TB, especially for rifampicin resistance. However, it may not detect certain mutations related to isoniazid resistance. Complementary tests like Xpert MTB/XDR or whole-genome sequencing could improve diagnostic accuracy and support more effective TB control strategies.